PONDOK PESANTREN (Lembaga Pembentuk Karakter Bangsa) - Syafe’i, Imam (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2014)
Degradation of morals, ethics and character today continues to be a major problem among teens this nation. Every action and behavior that are not based on religious values create patterns of teenage life of the Indonesian nation increasingly unfocused. Gambling, booze, brawls, sex continues to take its toll, but the culprit it more and more so it is necessary to find the problem its grass roots to be resolved. The presence of a boarding school can be an alternative moral issues, ethics and character of Indonesian adolescents. Pesantren is a multi-religious educational institutions function, as well as educational institutions to transfer religious sciences (tafaqquh fi al-din) and the values of Islam religious boarding school as an institution of social control, and boarding schools as religious institutions who do social engineering or community development.